Vadim Shershenevich as a translator, librettist and critic in a theatrical dialogue with Shakespeare - D. N. Zhatkin; V. V. Serdechnaya (Научный диалог)
The reception of the works of William Shakespeare in the work of the poet and translator Vadim Shershenevich (1893—1942) is considered. The relevance of the study is due to the insufficient study of the reception of Shakespeare’s work in the legacy of Shershenevich. The novelty of the study lies in the reference to the little-known texts by Shershenevich, which are translations and adaptations of Shakespeare’s plays for the early Soviet theater, as well as in understanding the specifics of the perception of these theater projects in the press of the 1920s—1930s. Particular attention is paid to archival documents, which make it possible to recreate in detail the landscape of the literary and theatrical process of that period. It is proved that Shershenevich became the author of adapted texts for three productions based on Shakespeare in pre-war Moscow: «Romeo and Juliet» at the Chamber Theater (1921), «Hamlet» in the version of A. Dumas at the «Romanesque» Theater (1923, work on the performance stopped in rehearsal time), “The Twins” based on the play “Twelfth Night” at the Moscow Operetta Theater (1939). The concept of two translation approaches in the work of V. Shershenevich is proposed: an accurate literary translation (this is how he translates «King John» and «Cymbeline») and an adapted translation for theatrical needs.